Comparison of Histological Changes in Mice Infected with the Cryptosporidium Parvum after Treatment with an Aquatic Leaf Extract of Salvia Officinalis, Pimpinella Anisum and, Spiramycin Drug - Khadiji Khleaf Al-Dulaimi; Karama Tahreer Ahmed Al-Taee; Thaer Abdulqader Salih (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Cryptosporidium parvum was cause Cryptosporidiasis .In this study the therapeutic effectof two aquatic extracts of plants in infected white mice with the C. parvum were examined and the resultswere compare with the therapeutic effect of Spiramycin through the study of the histological changes inmouse intestine. Methods: Thirty male mice were divided into six groups: group 1(non infected, negativecontrol ), group 2 (feeding with C. parvum oocysts, positive control ), group 3 (infected and treatment withleaf extract of Pimpinella anisum), group 4 (infected and treated with Salvia officinalis extract ,the group5 and 6 (infected and treatment with 5mg and 10mg Spiramycin Respectively ) The existence of oocystsin the feces of animals was counted daily during the therapeutic period .After two weeks; the changes ofcecum histological sections were examined. Conclusions: The oocysts counted in feces samples, showedsignificant differences between the treatments (P <0.05). The cecum histological changes in the group 3and 4 indicated that leaf extract of plants have moderate efficacy in treatment of C.parvum infection. Thececum appears close to normal at the concentration of 5mg Spiramycin there is no abnormal tissue in theconcentration of 10 mg.